Eksplorasi Program 'Sekolah Orang Tua Hebat' untuk Meningkatkan Peran Orang Tua dalam Pengasuhan Anak Usia Dini di Desa Alas Tengah Paiton - Mahfudz, Ali (Universitas Islam Zainul Hasan Genggong, 2025)
Early childhood is an important stage in human life where child development reaches its peak (golden age) because children's brain and physical growth are optimal. The role of parents in mentoring is needed to further optimize children's development and growth. However, parental involvement in early childhood care is often lacking due to several factors such as work, limited parenting competence, and divorce. lack of parental involvement can be an obstacle in the process of child development. Therefore, in Alastengah Paiton Village, the 'Great Parent School' program was initiated as an effort to improve the role and involvement of parents in early childhood care. Through a qualitative approach with data collection techniques through interviews and documentation. The results showed that the 'Sekolah Orang Tua Hebat' program is effective in improving the role of parents in early childhood care. Parents have increased knowledge and skills in understanding the needs of their children.